STUDI PSIKOLOGI SIBER TENTANG DAMPAK HATE SPEECH BAGI PENGGUNA MEDIA SOSIAL - Abdillah, Rijal; Aulia Ibrahim, Amanda; Odelia Emmanuelha Sirait, Nadine; Krissan Oktavia, Nadya; Widyadari, Rica; Febriyanti Amanda, Shalbina; Nabila Jansa, Siti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
A person can now more easily access a variety of information through social media in a meeting room thanks to increasingly sophisticated information technology. Numerous social media platforms, such as WhatsApp, Line, Facebook, Twitter, Youtube, TikTok, and Instagram, constantly highlight certain things that the user should consider when engaging with those platforms. However, very few people who use social media or the internet communicate with other online users to give them advice. Therefore, the purpose of this study is to examine the phenomenon of hate speech from the viewpoint of those who use social media. Data is obtained by using an in-depth interview with eight people who use social media. Purposive sampling is a technique that is employed in qualitative phenomenology as a means of collecting data from study subjects. Data from the analysis of the case study were redacted, displayed, and verified using data phenomenology analysis. The current study produces the following results: In the beginning, the topic was social media. Second, Netizens on social media are also alerted. Third, Hate speech. Fourth, the impact of hate speech. Fifth, Ethical standards in social media comments. Various studies have been conducted to determine the subjectivity of hate speech in social media. It is hoped that the results of this study would help those who use social media avoid embarrassment when commenting on social media.